Analisi Kompilasi Hukum Ekonomi Syariah (KHES) dan KUHPerdata terhadap Praktik Sewa Menyewa Rumah Bersyarat - Siti Asiyah Nur Arifah; Udin Saripudin; Neng Dewi Himayasari (UNISBA Press, 2024)
Abstract. The practice of renting a house in Winduhaji Village, Sedong District, Cirebon Regency is carried out orally with several conditions given by the homeowner. These conditions include the tenant's responsibility for the damage that occurs and the tenant's obligation to maintain the house properly. However, it turned out to be a debate for both parties. This study aims to understand the practice of conditional renting houses in Winduhaji Village, Sedong District, Cirebon Regency, and analyze it based on the Compilation of Sharia Economic Law (KHES) and the Civil Code. This research method uses a qualitative approach with the type of normative–empirical research. Primary and secondary data are used as data sources, as well as data collection methods include observation, interviews, documentation, and literature studies. The data obtained was then analyzed using the qualitative descriptive data analysis method. The results of the study show that the practice of renting a conditional house in Winduhaji Village, Sedong District, Cirebon Regency is carried out orally without written evidence. Homeowners provide relatively cheap prices and do not provide a definite time limit for payment. However, the landlord gives several conditions to the tenant, such as taking good care of the house, cleaning all parts of the house, and fixing the damage with funds from the tenant. Based on the analysis of KHES and the Civil Code, the practice of renting a house in Winduhaji Village, Sedong District, Cirebon Regency is said to be null and void because of several conditions that are not by the provisions of the law. These conditions include Article 306, Article 313 (2), and Article 305 of the Criminal Code, as well as Articles 1320 (1) and (4), Article 1550 (2) and (3), and Article 1560 (1) of the Civil Code. Abstrak. Praktik penyewaan rumah di Desa Winduhaji, Kecamatan Sedong, Kabupaten Cirebon, dilakukan secara lisan dengan sejumlah syarat yang ditetapkan oleh pemilik rumah. Syarat-syarat tersebut mencakup tanggung jawab penyewa atas kerusakan yang terjadi serta kewajiban penyewa untuk merawat rumah dengan baik. Namun, hal ini menimbulkan perdebatan antara kedua belah pihak. Penelitian ini bertujuan untuk memahami praktik sewa rumah dengan syarat di Desa Winduhaji serta menganalisisnya berdasarkan Kompilasi Hukum Ekonomi Syariah (KHES) dan KUH Perdata. Metode penelitian menggunakan pendekatan kualitatif dengan jenis penelitian normatif-empiris. Data primer dan sekunder digunakan sebagai sumber informasi, dengan metode pengumpulan data meliputi observasi, wawancara, dokumentasi, dan studi pustaka. Data yang diperoleh dianalisis menggunakan metode analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa praktik sewa rumah dengan syarat di Desa Winduhaji dilakukan secara lisan tanpa bukti tertulis. Pemilik rumah menetapkan harga sewa yang relatif murah tanpa batasan waktu pembayaran yang jelas. Namun, pemilik rumah memberikan beberapa syarat kepada penyewa, seperti menjaga rumah dengan baik, membersihkan seluruh bagian rumah, dan memperbaiki kerusakan dengan biaya dari penyewa. Berdasarkan analisis KHES dan KUH Perdata, praktik sewa rumah di Desa Winduhaji ini dianggap batal demi hukum karena beberapa syarat yang tidak sesuai dengan ketentuan hukum. Syarat-syarat tersebut melanggar Pasal 306, Pasal 313 (2), dan Pasal 305 KHES, serta Pasal 1320 (1) dan (4), Pasal 1550 (2) dan (3), dan Pasal 1560 (1) KUH Perdata.